Evaluation of video self‐instruction for implementing paired‐stimulus preference assessments. Issue 3 (17th May 2018) - Hansard, Candice; Kazemi, Ellie
Abstract : We trained four undergraduate students who reported no prior experience implementing behavior‐analytic procedures to conduct a paired‐stimulus preference assessment using a video self‐instruction package. The package was composed of several components from prior research (i.e., a voice‐over script, written instructions, multiple video models per step, and instructions for the trainee to rehearse throughout the video presentation). We used a nonconcurrent, multiple‐baseline‐across‐participants design and found that all participants accurately implemented the preference assessment with a simulated client after viewing the video once. We discuss the contributions of the current results and directions for future research on video self‐instruction for staff (i.e., maintenance, generalization, social validity).